Peningkatan Kesadaran Kebersihan Jama’ah Melalui Penyediaan Tong Sampah Di Area Masjid: Studi Kasus KKN Tematik Di RT 08 Pematang Gubernur - Nopentri, Elvemas; Anggara , Yogi; Herey , Fadhel Alfarozi; Manurung , Niko Demus; Rhamadan , Danny; Putra, Dwingki Marta; Susena, Karona Cahya; Gayatri, Ida Ayu Made Er Meytha (Universitas Dehasen Bengkulu, 2025)
Low awareness of proper waste disposal among mosque congregants often causes cleanliness issues. The KKN Tematik program in RT 08 Pematang Gubernur aimed to improve cleanliness by providing garbage bins at strategic points in the mosque area. This study used a qualitative case study method with observation, interviews, and documentation. The results show that the garbage bins made it easier for congregants to dispose of waste properly, improved overall cleanliness, and encouraged new habits of keeping the mosque environment clean. Support from mosque management and regular education were key to the success of this program.